Habilidades motoras relacionadas à aquisição da escrita manual em estudantes na fase pós-caligráfica - Marques, Valéria de Cássia [UNIFESP] (2017)
Objective: The present study evaluated the quality of manual writing in motor aspects and speed and readability performance in children and adolescents, in the post calligraphic phase, with and without complaints of handwriting development. Its objective was to investigate the motor skills pattern of the Manual writing in adolescents, post-calligraphic phase, with and without writing complaints and to verify if there are significant differences in writing performance between the groups. Methods: For this, the design was prospective, transversal and quantitative, initially in a convenience sample of 23 children and adolescents aged 12 years to 16 years and 11 months, whose average age was 12 years and 11 months, regularly enrolled in public and private schools, of the regular education network, with and without complaints of learning and writing development. Results: Statistical significance was obtained for the greater writing speed in the group of children without complaints, and the identification of the presence of writing instrument (pencil or pen) in both the sample with and without written complaints considered inferior to the execution of this function. Being the highest percentage of pretensions considered inferior, found in the group with complaints. Conclusion: The variables that proved to have a more agile motor profile in the writing of schoolchildren without complaint in the learning and development of manual writing were identified. There is similarity in performance in the way the letters are traced, in the form of apprehending the pencil and in the posture of upper limb and body, which need to be discussed and traced.